Language skills in children with benign childhood epilepsy with centrotemporal spikes: a systematic review - Teixeira, Joana (2019)
Benign childhood epilepsy with centrotemporal spikes (BECTS) is the epileptic syndrome that most affects preschool and school-age children. Despite being usually considered a benign condition, several studies have shown that this epileptic syndrome is responsible for cognitive morbidities in children, namely at the level of attention and memory, as well as language. However, language disorders are still superficially addressed by the literature. This review aimed to compile and synthesize recent literature in this area. This systematic bibliographic research comprises studies published between 2005 and 2016 in PubMed, Science Direct, and PsycInfo computer databases that included the keywords “language”, “cognition”, “benign childhood epilepsy with centrotemporal spikes”, “rolandic epilepsy”, and “children”. Studies were selected according to the following criteria: (i) published in scientific peer reviewed journals; (ii) performed with children between the ages of 3 and 16 years; and (iii) performed in children with BECTS in the active phase or after remission. Eighteen studies met these criteria. Nine studies mentioned language skill disorders in children with BECTS in the receptive and productive domains of semantics and seven studies in morphosyntax. Regarding phonological awareness, six studies have found limitations in the intrasyllabic, syllabic, and phonemic levels. These studies have also detected deficits in verbal fluency (semantic and phonemic) and in verbal memory. Because of the heterogeneity of the study samples and the use of innumerable distinct tasks in the evaluation of language skills, the results obtained still show some lack of consensus regarding the affected areas. Despite this, it was possible to synthesize and define more precisely the oral language variations presented by this population. We have concluded that the changes in semantic skills are the most frequently mentioned. The studies have also showed morphosyntactic and phonological disorders, in spite of showing some variability among them.